ANALISIS PENGARUH PEMASARAN MEDIA SOCIAL, REPUTASI INFLUENCER DAN DISKON HARGA TERHADAP KEPUTUSAN PEMBELIAN IMPULSIF MELALUI KEPERCAYAAN MEREK SEBAGAI VARIABEL INTERVENING (Studi Pada Pengguna Tiktok Shop Di Kota Semarang) - Gracelia, Yohana; Indriani, Farida (Diponegoro Journal of Management, 2023)
ABSTRACT The Covid – 19 pandemic has had many detrimental effects, one of which is the decrease in MSME income which has caused many businesses to have to go out of business, as for ways to overcome these problems by keeping up with the times and changing the sales system from initially offline to online. One way is to use social media as a means of promotion and attracting consumers to make purchases. One of the social media used is Tiktok, Tiktok is a social media platform from China which is currently also creating online shopping features for its users. This study aims to determine the effect of Social Media Marketing, Influencer Reputation, and Discounted Prices on Brand Trust which encourages consumers to make impulsive buying decisions. This research was conducted using a survey method with a Goggle Form questionnaire given to users of the Tiktok Shop Platform. Methods of data collection using purposive sampling. In this study tested using 100 samples obtained from the questionnaire. The data is processed using the PLS (Partial Least Square) analysis technique through the SmartPLS V.4 software. The results of this research data processing indicate that Social Media Marketing, Influencer Reputation, and Discount Price have a positive influence on Brand Trust. In addition, this study also shows that Brand Trust has a positive influence on Impulsive buying decisions.